(untitled) (The Review of Diabetic Studies, 2024)
Acute surgical care demands rapid, coordinated management of complex, time sensitive conditions. This comprehensive review examines the essential role of the interdisciplinary team (IDT) in optimizing outcomes for patients undergoing emergency or high acuity surgery, with a specific focus on five core disciplines: respiratory therapy, nursing, radiology, pharmacy, and surgery. The review synthesizes evidence from the past two decades, highlighting how each discipline contributes uniquely to perioperative care while emphasizing that effective collaboration is the key to preventing complications, reducing mortality, and improving patient safety. Respiratory therapists play a critical role in preventing and managing postoperative pulmonary complications through lung expansion maneuvers, non invasive ventilation, and airway clearance. Nursing serves as the central coordinator of perioperative safety, ensuring continuity across handoffs, early recognition of deterioration, and activation of rapid response systems. Radiology provides rapid diagnostic accuracy and minimally invasive image guided interventions that often replace traditional open surgery. Pharmacy leads medication safety, antimicrobial stewardship, and multimodal pain management, reducing adverse drug events and opioid related harm. Surgery has evolved from a hierarchical, surgeon centric model to a collaborative leadership approach that empowers all team members to speak up and share decision making. However, significant barriers persist, including hierarchical culture, communication failures, physical separation of team members, after hours coverage gaps, lack of shared mental models, inadequate team training, electronic health record design flaws, and workload pressures. Overcoming these barriers requires a systematic strategy: flattening hierarchy through psychological safety and empowerment, adopting standardized communication tools (SBAR, I PASS, closed loop communication), implementing daily interdisciplinary rounds, investing in 24/7 specialist coverage or telemedicine, integrating interprofessional education and simulation based team training, redesigning EHRs for shared team documentation, and measuring teamwork metrics with regular feedback. Evidence from high reliability organizations and healthcare implementation studies demonstrates that such interventions reduce surgical complications, shorten hospital stays, decrease medication errors, lower mortality, and improve staff satisfaction. This review concludes that the interdisciplinary team is not an optional adjunct but a core component of high quality acute surgical care, and that sustained, multi level efforts to overcome collaboration barriers will define the future standard of care.Acute surgical care demands rapid, coordinated management of complex, time sensitive conditions. This comprehensive review examines the essential role of the interdisciplinary team (IDT) in optimizing outcomes for patients undergoing emergency or high acuity surgery, with a specific focus on five core disciplines: respiratory therapy, nursing, radiology, pharmacy, and surgery. The review synthesizes evidence from the past two decades, highlighting how each discipline contributes uniquely to perioperative care while emphasizing that effective collaboration is the key to preventing complications, reducing mortality, and improving patient safety. Respiratory therapists play a critical role in preventing and managing postoperative pulmonary complications through lung expansion maneuvers, non invasive ventilation, and airway clearance. Nursing serves as the central coordinator of perioperative safety, ensuring continuity across handoffs, early recognition of deterioration, and activation of rapid response systems. Radiology provides rapid diagnostic accuracy and minimally invasive image guided interventions that often replace traditional open surgery. Pharmacy leads medication safety, antimicrobial stewardship, and multimodal pain management, reducing adverse drug events and opioid related harm. Surgery has evolved from a hierarchical, surgeon centric model to a collaborative leadership approach that empowers all team members to speak up and share decision making. However, significant barriers persist, including hierarchical culture, communication failures, physical separation of team members, after hours coverage gaps, lack of shared mental models, inadequate team training, electronic health record design flaws, and workload pressures. Overcoming these barriers requires a systematic strategy: flattening hierarchy through psychological safety and empowerment, adopting standardized communication tools (SBAR, I PASS, closed loop communication), implementing daily interdisciplinary rounds, investing in 24/7 specialist coverage or telemedicine, integrating interprofessional education and simulation based team training, redesigning EHRs for shared team documentation, and measuring teamwork metrics with regular feedback. Evidence from high reliability organizations and healthcare implementation studies demonstrates that such interventions reduce surgical complications, shorten hospital stays, decrease medication errors, lower mortality, and improve staff satisfaction. This review concludes that the interdisciplinary team is not an optional adjunct but a core component of high quality acute surgical care, and that sustained, multi level efforts to overcome collaboration barriers will define the future standard of care.